Adult attachment and long-term singlehood. (February 2019) - Pepping, Christopher A; MacDonald, Geoff
Highlights: Attachment orientations have implications for understanding singlehood. Attachment orientations may differentially predict reasons for singlehood. Sub-groups of singles are likely to differ in life outcomes. Abstract : Rates of singlehood are increasing rapidly in the Western World. In the current paper, we discuss the phenomenon of long-term singlehood from an attachment perspective, outline three distinct sub-groups of singles (anxious, avoidant, and secure), and demonstrate the utility of these groups by highlighting their unique characteristics and possible life outcomes, including factors that may moderate these outcomes. Finally, we offer suggestions for future research to enhance our understanding of this vastly under-researched population.